Sanctuary for vulnerable Arctic species at the Borealis Mud Volcano - Giuliana Panieri; Claudio Argentino; Alessandra Savini; Bénédicte Ferré; Fereshteh Hemmateenejad; Mari H. Eilertsen; Rune Mattingsdal; Sofia P. Ramalho; Tor Eidvin; Sarah Youngs; Beckett Casper Colson; Anna Pauline Miranda Michel; et al. (Nature Communications)
Abstract Borealis is a recently discovered submerged mud volcano in the Polar North Atlantic, differing from the numerous methane seepages previously identified in the region. Here we show in situ observations from a remotely operated vehicle (ROV), capturing the release of warm (11.5 °C) Neogene sediments and methane-rich fluids from a gryphon at Borealis. The surrounding seafloor within the mud volcano features extensive carbonate deposits, indicating prolonged diffuse methane migration. Sampling and imagery reveal that Borealis supports unique habitats adapted to low-oxygen conditions near methane seeps. Additionally, the irregularly shaped carbonate structures serve as a natural shelter from bottom trawling and a substratum for sessile fauna and may function as nursery grounds for threatened fish species. This discovery underscores the ecological significance of cold seep ecosystems in the Polar North Atlantic, highlighting their role in biodiversity by serving as refuges for marine species and emphasizing the need for their conservation.